Dynamics of Competition in the Marine Aquaculture Industry: A Research on Turkey - ARSLAN, FATMA MÜGE; UZMANOĞLU, MUSTAFA SELÇUK (My University, 2020)
In this study, dynamics of competition in the marine fish culture industry in Turkey is investigated. Today, with thedevelopment of technology people's access to information has facilitated. People, with access to information, began to giveimportance to - healthful nutrition. Therefore; as a source of healthful protein, the demand for fish is increasing day by day.Also, this increase in demand motivates the growth of the fish farming industry intensively. Consequently the production offishery products is growing almost without any problem. Enterprises that are reaching higher levels in technical knowledgeon aquaculture- face fierce competition with each other. This study aims to uncover the dynamics of competition in themarine aquaculture industry by evaluating the perceptions of different parties such as: aquaculture enterprises, feedproducers, processing enterprises, the ministry, universities, retail businesses, research institutes, and suppliers that take placein the sector. The survey prepared for this purpose was conducted with 344 people. Results were evaluated and interpretedboth as a whole and separately according to business types in the sector. The results show that in the marine aquacultureindustry, selling prices of products, quick delivery of products to the market, and financial power are the most importantdynamics of competition.

Bu çalışmada Türkiye’de deniz balığı yetiştiriciliği sektöründe rekabet dinamikleri incelenmiştir. Günümüzde_x000D_ teknolojinin gelişmesiyle beraber insanların bilgiye ulaşması kolaylaşmıştır. Bilgiye ulaşma ile beraber insanlar sağlıklı_x000D_ beslenmeye önem vermeye başlamışlardır. Bu nedenle sağlıklı protein kaynağı olan balığa talep gün geçtikçe artmaktadır. Bu_x000D_ artan talep nedeniyle de balık yetiştiriciliği sektörü her geçen yıl büyümeye devam etmektedir. Günümüzde artık balık_x000D_ üretiminde sıkıntılar yaşanmamaktadır. Yetiştiricilikte teknik bilgi anlamında üst seviyelere ulaşan işletmeler birbirleriyle_x000D_ yoğun rekabet içerisine girmektedirler. Bu çalışmanın amacı, deniz balığı yetiştiriciliği sektöründe artan rekabet dolayısıyla_x000D_ sektörde yer alan yetiştiriciler, yem üreticileri, işleme işletmeleri, bakanlık çalışanları, üniversiteler, perakende işletmeler,_x000D_ araştırma enstitüleri ve tedarikçi işletmelerde çalışanların sektörde rekabet dinamiklerini nasıl algıladıklarını ortaya_x000D_ koymaktır. Bu amaçla hazırlanan anket 344 kişi ile gerçekleştirilmiştir. Bulgular sektörde yer alan işletme tiplerine göre ayrı_x000D_ ayrı ve toplu olarak değerlendirilmiş ve yorumlanmıştır. Sektörde ürünün satış fiyatı, finansal güç ve pazara hızlı ürün_x000D_ sunmanın rekabette en önemli dinamikleri oluşturduğu belirlenmiştir._x000D_
Deniz Balıkları Yetiştiriciliği Sektöründe Rekabet Unsurları: Türkiye Üzerine Bir Araştırma